Improved estimates of net ecosystem exchanges in mega-countries using GOSAT and OCO-2 observations - Lingyu Zhang; Fei Jiang; Wei He; Mousong Wu; Jun Wang; Weimin Ju; Hengmao Wang; Yongguang Zhang; Stephen Sitch; Jing M. Chen (Communications Earth & Environment)
Abstract Accurate national terrestrial net ecosystem exchange estimates are crucial for the global stocktake. Net ecosystem exchange estimates from different inversion models vary greatly at national scale, and the relative impacts of prior fluxes and observations on these inversions remain unclear. Here we estimate the net ecosystem exchange of 51 land regions for the 2017-2019 period, focusing on the 10 largest countries, using prior fluxes from 12 terrestrial biosphere models and XCO2 retrievals from GOSAT and OCO-2 satellites as constraints. The average uncertainty reduction for the 10 countries increases from 37% with GOSAT and 45% with OCO-2 to 50% with combined observations, indicating a trend towards robust estimates. At finer spatial scales, even with combined observations, the uncertainty reduction is only 33%, i.e., the prior flux dominates the estimates. This finding underscores the critical importance of integrating multi-source observations and refining prior fluxes to improve the accuracy of carbon flux estimates.